HUBUNGAN INTENSITAS INTERAKSI DENGAN TEMAN SEBAYA DAN PENGGUNAAN BAHASA GAUL PADA ANAK SD - Luncana Faridhah Sasmito; Eny Kusumawati; Sekar Wulan Prawesti; Erlando Nanda Bagus Paskal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The use of slang among elementary school children is increasing along with the use of digital media and peer interactions. Although this phenomenon shows that the social environment plays an important role in shaping children's communication patterns, there is still little research examining the relationship between the intensity of peer interaction and the use of slang in elementary schools. The aim of this study is to examine how the intensity of peer interactions and the use of slang among students at SDN Purworejo Banjarsari Surakarta are related to each other. This study conducted quantitative research with a correlational design. There are 120 students in grades IV, V, and VI, aged between 7 and 10 years, who are the subjects of the study. Data were collected through non-participatory observation, interviews, and questionnaires. The validity and reliability tests of the research instruments have been conducted, and the data were analysed at a significance level of 5% using descriptive statistics, normality tests, linearity tests, and Pearson correlation tests. The research results show that the intensity of peer interaction is in the high category with an average score of 78.43 ± 6.82, and the use of slang is also in the high category with an average score of 74.91 ± 7.14. Observation and interview results indicate that peers use slang more frequently in informal communication. On the other hand, students tend to use Indonesian in formal contexts. This study found that the intensity of peer interaction correlates with a higher level of slang used by elementary school students. Therefore, teachers and educational institutions should develop contextual Indonesian language learning so that students can use different language varieties appropriate to various communication situations.